Removal of Microorganisms in Drinking Water using Pulsed High Voltage - Ariadi Hazmi; Reni Desmiarti; Eka Putra Waldi; D. Darwison (Institute for Research and Community Services, Institut Teknologi Bandung, 2013)
A pulsed high voltage was used to remove microorganisms in drinking water. The effects of the pulsed high voltage on pH, conductivity, temperature and oxidation reduction potential (ORP) of the drinking water were investigated. The observed results show that the removal efficiency with respect to fecal coliforms and total coliforms increased with the increase of the pulsed high voltage. The removal efficiency for microorganisms such as fecal coliforms and total coliforms was in the range 25-100% and 44-100%, respectively, after the water was exposed to a pulsed high voltage of 5-10 kV for 60 minutes. An increase of the pulsed high voltage caused a decrease in the conductivity and ORP with operational time.